El planeamiento tributario y su efecto en la situacion financiera de la Empresa de Transporte Turismo Erick El Rojo S.A., distrito de Trujillo, período 2015. - Ciudad Fasanando, Sharon Isabel (2016)
The objective of this research was to determine the effect of tax planning in the financial position of the company "Erik the Red", based on a descriptive comparative research with cross non-experimental design, sample consisted of financial statements ( results and overall) balance of the last three years and the counter Trujillo agency (as is observing the sample was based on nonprobability sampling); in the case of the counter, the data were obtained based on an interview guide structure directed to the counter, qualified in levels of agreement regarding assumptions regarding the tax regulations (designed in positive orientation greatly and some negatively oriented) then be rated based on the level of tax planning, also verified the tax burden as another dimension of tax planning; in the case of the financial situation was analyzed based on liquidity ratios, solvency and profitability I indebtedness. The investigation concluded that the company has a negative liquidity, being that does not exceed the unit; which puts her in critical situation if I had to liquidate; on the other hand instability in the return on equity capital, it would be associated with the unstable solvency, as would evidence an imbalance between the level of indebtedness and ability to cushion the effect of such borrowing, thus to effectively manage assets those provisions; ie although the company further works with third-party resources, however must balance the effect of this and in the case the tax effect, as evidenced by the unstable tax burden that has submitted attributable to poor management planning tax.